PENINGKATAN HASIL BELAJAR MATA KULIAH PEMBELAJARAN BERBANTUAN KOMPUTER DENGAN MODEL PEMBELAJARAN DRILL AND PRACTICE - Syaad Patmanthara (SENTIA 2016, 2016)
Learning course on Computer Assisted Learning (CAL) in Information Engineering Education Study Program of UM apply contextual learning model. The learning model is done by connecting the subject matter with real activities or tailored to real-world situations by promoting practical activities in the learning activities. Contextual learning model applied such a positive impact that is able to help students to achieve competence in the areas of skills. However, this model has not been able to help students achieve competence in the realm of knowledge. Therefore we need a learning model that can increase the value of student knowledge. One model of learning that can be applied is drill and practice. The method used in this study is a quasi-experimental and descriptive. A quasiexperimental research designs is used to determine the effect of drill and practice learning model for learning outcomes and student retention. While descriptive study used to describe implementation ofdrill and practice learning model. The results of this study indicate that there are significant drill and practice learning model for learning outcomes aspects of the student's knowledge in the subject CAL. There is the influence of drill and practice learning model on the retention of students on CAL courses and there are significant aspects of the learning outcomes of knowledge on the retention of students on CAL courses that learned to drill and practice learning model.